Effects of institutional quality and the development of the banking system on corporate debt - Tresierra, Alvaro Edmundo (2018)
Purpose. This study aims to determine if the quality of national institutions and banking development condition the maturity of debt depending on the horizon of short or long term. Design/methodology/approach. Analysis is performed on a sample of 116 nonfinancial companies from Peru and Brazil. The measures of quality of national institutions and banking development were obtained from World Bank data and included factorial analysis for dynamic considerations. Findings. The findings, through the treatment of pointed indicators, the factor analysis and the subsequent estimation of a dynamic econometric model, called GMM-SYS, show that institutional quality fosters the maturity of long-term debt and banking development boots short-term financial relations. Research limitations/implications. Evaluating different measures of the quality of national institutions and banking development is necessary to demonstrate the robustness of the results beyond the sample evaluated in Latin America. Practical implications. The research allows to understand the interaction between national institutions and system banking through debt maturity, and this is useful for establishing common target between both groups. Social implications. It is important for corporate finance to understand the mechanisms of the interaction between national institutions and system banking, because this affects internal decisions of firms regarding financial implications. Originality/value. The treatment of measures of national institutions and banking development include dynamic considerations, and the application of this study in Latin America provides new findings regarding these kind of indexes and their interaction with firms¨ features such as debt maturity. Doi: https://doi.org/10.1108/JEFAS-03-2017-0053